Students’Ability in Reading TOEFL - Helena Badu (Jambura Journal of English Teaching and Literature, 2020)
TOEFL is a standardized test which measures the students’ skill and ability in English. This test is one of the requirements for English Department students before they take the theses examination. Hence, the students must be prepared well before taking the test in order they can get the standard score of TOEFL as has been required by English study program. During the pre-observation, it has been found that many students of English study program still have difficulty in having the TOEFL test that it finally gives impact on their TOEFL scores. For this reason, this research is conducted as an effort to analyze and get information about the students’ ability in TOEFL test, especially in the reading test. This research is analyzed qualitatively by taking the English Department students as the participants. The data are collected by using two instruments; observation and documentation, and it analyzes through some steps such as identifying the result of students’ test and analyzing them to obtain the answer of the research question. This research analyzes the students’ ability in reading toefl refers to Philips’ theory in toefl reading skill. The result of this research shows that the students have a high percentage in find pronoun referents. While find definition from structural clues is the lowest one. Thus, the students and lecturers should pay more attention to the strategies in reading toefl and have more practice in doing the test.